Growth and characterization of the oxide scales and core/shell nanowires on Ti-6Al-4 V particles during thermal oxidation - Arafat, M.M.; Haseeb, A.S. Md. Abdul; Akbar, S.A. (Elsevier, 2015)
Nanowires were grown on as-received and milled particles of Ti-6Al-4 V (Ti64) alloy under an optimum condition of 750 degrees C in an Ar atmosphere containing 15 ppm of oxygen. The as-grown nanowires and the underneath oxide scales developed on Ti64 particles were characterized by X-ray diffiactometry (XRD), field emission scanning electron microscopy (FESEM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), scanning transmission electron microscopy (STEM) equipped with energy dispersive X-ray spectroscope (EDS). Results revealed the formation of oxide scales consisting of double layers on the surface of Ti64 particles. The outer oxide scale was a mixture of Al2O3 and TiO2 whereas the inner oxide scale was solely TiO2. An unoxidized core was present inside depending On the size of the Ti64 particles at the initial state. The thickness of the outer oxide scale was also dependent on the size of the Ti64 particles. The nanowires grew in the outward direction from the outer oxide scale during thermal oxidation. The as-grown nanowires had fine and thick dimensions. Both types of nanowires had a core-shell structure where the core was made of TiO2 and the shell was Al2O3. It was seen that both residual and induced stress played a role for the growth of nanowires on Ti64 particles during thermal oxidation. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.